2022
DOI: 10.1101/2022.04.11.22273688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing patterns in reporting and sharing of review data in systematic reviews with meta-analysis of the effects of interventions: a meta-research study

Abstract: Objectives: To examine changes in completeness of reporting and frequency of sharing review materials in systematic reviews (SRs) over time; and factors associated with these changes. Methods: We examined a random sample of 300 SRs with meta-analysis indexed in PubMed, Science Citation Index, Social Sciences Citation Index, Scopus and Education Collection in November 2020. We compared the extent of complete reporting in these reviews against 110 SRs indexed in MEDLINE in February 2014. We examined associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…Other types of review materials that provide details of the data preparation and statistical analyses, including analytic code, files showing data conversion and imputations, and unprocessed extracted data, were not as frequently shared. This infrequent sharing of these review materials has been reported in other studies [10, 39, 43]. It is possible that some participants did not report sharing analytic code simply because their meta‐analytic software do not require coding (e.g., Review Manager or Comprehensive Meta‐Analysis).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Other types of review materials that provide details of the data preparation and statistical analyses, including analytic code, files showing data conversion and imputations, and unprocessed extracted data, were not as frequently shared. This infrequent sharing of these review materials has been reported in other studies [10, 39, 43]. It is possible that some participants did not report sharing analytic code simply because their meta‐analytic software do not require coding (e.g., Review Manager or Comprehensive Meta‐Analysis).…”
Section: Discussionsupporting
confidence: 56%
“…Mandates from major public funders, such as one recently issued by the US National Institutes of Health (NIH) [5], are expected to accelerate the normalization of data sharing practices. However, as these initiatives tend to target clinical trials and basic science [6,7], the evidence synthesis research landscape is still plagued by low availability of data and code [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We anticipate the same for PRISMA 2020 93 given its copublication in multiple high-impact journals. However, to date, there is a lack of strong evidence for an association between improved systematic review reporting and endorsement of PRISMA 2009 standards 43,111 . Most journals require a PRISMA checklist accompany submissions of systematic review manuscripts.…”
Section: Uptake and Impactmentioning
confidence: 99%
“…These have concentrated on evidence searching 40 and selection given how demanding it is for humans to maintain truly up-to-date evidence 2,41 . Cochrane has deployed machine learning to identify randomized controlled trials (RCTs) 2 and studies related to COVID-19 42 , but such tools are not yet commonly used 43 . The routine integration of automation tools in the development of future evidence syntheses should not displace the interpretive part of the process.…”
Section: Influences On the State Of Evidence Synthesismentioning
confidence: 99%
“…(Ten reviews were excluded from the original sample of 300 reviews, either because they were COVID-19 reviews, or the online publication date could not be determined.) This sample was derived for a separate project [14] and used stricter inclusion criteriasystematic reviews had to have clearly stated objective(s), report the sources searched, include an assessment of risk of bias, and contain at least one pairwise meta-analysis. For each review, one author (SM) extracted the date of search (including the format and where reported) and date the review was published online.…”
Section: Data Search Study Selection and Data Extractionmentioning
confidence: 99%